Glycoproteins Isolated from Tongkat Ali Plants Capable to elevate Testosterone in both in vitro and in vivo Experiments - Vejayan, Jaya; Fatinah, Ahmad; Sharifah Aminah, Tuan Said; Chakravarthi, Srikumar; Karikalan, Barani (Faculty of Pharmacy, University of Benin, 2024)
Tongkat Ali, a common name used to identify at least three plants, Eurycoma longifolia, Polyathia bullata, and Stema tuberosa, is recognized for its aphrodisiac bioactive constituent attributed to glycoproteins, particularly in E. longifolia. This study explores the presence and bioactivity of glycoproteins in P. bullata and S. tuberosa, employing similar extraction methods to E. longifolia. The crude extracts from all three plants were isolated, and glycoproteins were separated using lectin affinity chromatography. The glycoprotein yields were determined, and the protein characterization was conducted using Sodium Dodecyl Sulphate Gel Electrophoresis (SDS PAGE). Consequently, through both in vitro and in vivo experiments, the bioactivity of the isolated glycoproteins was tested for their ability to elevate testosterone levels. In vitro studies conducted on approximately 4000 TM-3 Leydig cells revealed that treatment with 50 µg/mL of glycoproteins extracted from P. bullata and S. tuberosa resulted in a notable increase in testosterone concentration by 45% and 48%, respectively, compared to the untreated cells after 72 h. Moreover, in groups of mice administered with the isolated glycoproteins for 20 days, testosterone concentrations increased by over 50% compared to the control groups. Despite the relatively low yields of glycoproteins, with only 0.26% and 0.21% present in the roots of P. bullata and S. tuberosa, respectively, their effectiveness was evident. This highlights that the aphrodisiac bioactive constituents, are glycoproteins, within all three Tongkat Ali plants.